2006
DOI: 10.2337/db05-1595
|View full text |Cite
|
Sign up to set email alerts
|

Altered Endothelial Nitric Oxide Synthase Targeting and Conformation and Caveolin-1 Expression in the Diabetic Kidney

Abstract: Experimental diabetes is associated with complex changes in renal nitric oxide (NO) bioavailability. We explored the effect of diabetes on renal cortical protein expression of endothelial NO synthase (eNOS) with respect to several determinants of its enzymatic function, such as eNOS expression, membrane localization, phosphorylation, and dimerization, in moderately hyperglycemic streptozotocininduced diabetic rats compared with nondiabetic control rats and diabetic rats with intensive insulin treatment to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 50 publications
5
66
0
Order By: Relevance
“…Tissue preparation and western blot analysis were performed as previously described 17,29 using the primary antibody raised against KDM6A (Abcam) or Ezh2 (Upstate, Billerica, MA, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Tissue preparation and western blot analysis were performed as previously described 17,29 using the primary antibody raised against KDM6A (Abcam) or Ezh2 (Upstate, Billerica, MA, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…The kidneys were homogenized in lysis buffer containing protease and phosphatase inhibitors and analysed by immunoblotting as previously described (Komers et al, 2006), using primary antibodies raised against phospho-serine 19-MLC (P-MLC, 1:800, Cell Signaling, Beverly, MA, USA cat. #3671); and ROCK1 and ROCK2 (1:500, BD Transduction Laboratoriesℱ, 2350 Qume Drive, San Jose, CA, USA, cat.…”
Section: Immunoblottingmentioning
confidence: 99%
“…For instance, diabetic persons often have poor peripheral circulation, which leads to ischemic injury, impaired wound healing, and impaired vision, all of which involve altered endothelial cell function that relates to endothelial nitric oxide (NO) synthase (eNOS) and the generation of NO (2,21). Several studies have shown that HDL acting through its receptor, SR-BI, can stimulate eNOS to produce NO (4,16,24,36).…”
mentioning
confidence: 99%